Accounting Technical Terms in Research Articles for Accounting Education: a Genre-Based Analysis - Djuwari Djuwari; Sasongko Budisusetyo (The Indonesian Accounting Review, 2024)
The importance of technical terms in the accounting field has garnered global attention, particularly for accounting education. Mastery of these specialized terms, which are commonly found in accounting research articles (ARAs), is essential for both students and researchers in the field. This study examines ARAs to identify the specific technical terms present in the introduction sections of various sub-genres of these articles. Data was collected from international journal articles available on Google Scholar and analyzed using genre-based analysis (GBA). The researchers first examined the rhetorical moves within each article, then identified the technical terms associated with these moves, and finally drew conclusions based on their findings. The study revealed that all ARAs included the complete set of rhetorical moves recommended for research articles, each containing specific accounting technical terms. In total, 99 technical terms were identified across 10 RAs, distributed throughout the rhetorical moves. This finding is particularly relevant for novice researchers and accounting educators. It is recommended that the accounting educators consider the technical term in the curriculum for accounting education. Besides that, for further research, researchers should also undertake similar studies for a broader perspective in accounting education.